(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Aim: During transition from childhood to adulthood, people are exposed to varioushazards having potentiality lead to unnatural deaths by distorting physical, mental and social wellbeing.Studying pattern of unnatural deaths helps stakeholders to formulate policies for prevention of loss ofimportant human resource.Materials and Methods: A descriptive study with purposive sampling was conducted at KIMS Hospital andResearch Centre, Bangalore from 2013 to 2015 wherein the data using pre-tested structured proforma wascollected from autopsies of unnatural deaths among pediatric age group (0-18 years). The details pertainingto the Socio demographic characteristics, pattern of injuries and cause of death was ascertained from thepolice reports, reliable attendants of the deceased, histopathological /hospital records and postmortemreports.The data obtained from this study was analyzed statistically by presenting the data in the form ofappropriate tables and graphs, computing the descriptive statistics like mean, median, standard deviationand percentages.Results: Out of 832 cases, 703 (84.5%) were unnatural deaths, amongst which 8.8% cases were of paediatricsof age group. In that (82.2%) 51 cases belonged to 12-18 years, followed by 5-12 years and preschool age(3-5years) each with 4 cases (6.5%), 3 cases (4.8%) are of toddlers (1-3) years and no cases were reportedamong infants. Male preponderance was seen 35 cases (56%). Maximum number of deaths occurred duringevening times i.e., 30 cases (48.39%).In the present study, maximum number of victims were from socialclass II i.e., 38 cases and least among social class I with only 1 case. Out of 62 cases , 37 cases (60%) wereintentional deaths (1 case (3%) is homicidal and 36 cases (97%) were suicidal )and 25 cases (40%)wereunintentional deaths. In the present study out of 36 suicidal cases, Hanging was the most preferred methodused to commit suicide with 26 cases (42%), followed by burns and drowning with 1 (8%) case each. Out 62cases, only 12 (19%) cases were treated before death and remaining 50 (81%) were not treated prior to death.Conclusion: This study indicates that there is an immense responsibility for the parents and caregivers insupervising their children .The public health burden of all unnatural deaths needs to be estimated to providea rational basis for policy decisions to implement necessary interventions.